The Interests of the European Union in Providing Cooperation and Verification Mechanism (CVM) Assistance to Bulgaria in the Midst of Euroscepticism - Eska Dwipayana Pulungan (Jurnal Hubungan Internasional, 2020)
This research aimed to describe the political map of the European Union (EU) in expanding its territory after the fall of the Berlin Wall. EU never granted membership status with special assistance to any country before. However, Bulgaria had received special membership assistance called the Cooperation and Verification Mechanism (CVM). The granting of this membership status was controversial because it was given when Euroscepticism was on its peak. Member countries such as the United Kingdom, Netherlands, and Germany considered that granting different membership status to fulfill the EU’s standards would aggravate the institutional performance. This case employed The Gains Of EU Enlargement to analyze what interests the EU wanted to gain in providing CVM assistance to Bulgaria. This approach explained, the EU wants to accelerate the Europeanization process of Bulgaria to reach the stabilization of European region security both internally and externally. However, external interests dominate the most, in order that EU can control the influence of Russia to Bulgaria. So, Bulgaria’s membership makes Russia unable to use its former ally as a propaganda tool to interfere in European affairs, especially regarding Russia's imported gas policy towards Europe.